Determinação da atuação dos RTKs na neuroindução e neurogênese de células-tronco adultas de tecido de cordão umbilical humano - Molina, Rachel Dias (2015)
Introduction : The cellular and physiological changes that accompany the aging process has pronounced effects in neurodegenerative diseases. Factors that produce neurodegeneration do so through different processes that culminate in a common signaling pathway cascade. Stem cells communicate via cellular signaling mechanisms, which is part of a complex system which governs and coordinates activities and cell functions. Understanding the mechanisms and forms of intercellular communication and their relationship in the activation of signaling cascades from the surface receptor to the cell nucleus during neurogenesis, will answer some pertinent questions to the mechanisms of action of stem cells in repair central nervous system. Objective : This study aimed to determine which RTKs being activated during neurogenesis of adult stem cells from human umbilical cord tissue. Methods : Adult stem cells were obtained from human umbilical cord tissue (n = 3) and subjected to specific inducers in neurodifferentiation means. The kit Human Phospho-RTK Array was used for evaluating the phosphorylation of the RTK and the expression determined by realtime PCR. Results : The mesenchymal stem cells obtained from umbilical cord tissue were confirmed by differentiation induction in adipocytes and osteocytes cells. The neurodifferentiation was confirmed by expression of genes that are expressed during neurogenesis in cells and neural cells, as well as immunocytochemistry technique markings which showed nuclear (DAPI) and cell processes (Fluoropan). During the neuroinduction processes and neurodifferentiation the phosphorylation levels of RTKs were variable, with no clear pattern. The Ryk receptor showed no significant changes in their levels of phosphorylation of the three samples studied and the different stages of differentiation, ie, mesenchymal, neuroinductions and neurodifferentiates cells. Conclusions : The tyrosine kinases are actively being phosphorylated during neuroinduction and neurogenesis, with varying standards between the different stages and between different samples, reflecting the variability of human adult stem cells.